Clinical anatomy : a core text with self-assessment - Monkhouse, Stanley (Edinburgh ; New York : Churchill Livingstone, 2001)
A short, highly readable, and well-illustrated book on anatomy, approached from the perspective of relating what medical students need to know about anatomy to the clinical work they will eventually be doing. The text includes a variety of self-assessment exercises to reinforce messages, test understanding, and help students prepare for exams
Sect. 1. Systematic anatomy. 1. Introduction. 2. Words and the anatomical position. 3. Outline of the body plan. 4. Skeleton and muscle. 5. Vertebral column. 6. Nervous system. 7. Cardiovascular system and lymph vessels. 8. Alimentary and respiratory systems. 9. Urogenital system -- Sect. 2. Regional anatomy. 10. Thorax. 11. Abdomen, pelvis and perineum. 12. Upper limb. 13. Lower limb. 14. Head and neck. 15. Brain. 16. Surface anatomy: revision
Includes index
Keywords: Human anatomy; Anatomy; Anatomy